RELIGION VIs-A-VIS MYSTICISM A Quest for the Meaningfulness of Life - Chackalackal, Saju (Journal of Dharma, 2011)
Human quest for the ultimate understanding of reality seems to be unquenchable. The rigour and ingenuity with which various intellectual disciplines have been formed and perfected over the centuries testify to the human ability to soar higher and higher, accessing the ever-deeper and unfathomable dimensions of reality. The undying and ever-stronger determination and commitment on the part of seekers to unravel the inner recesses of reality against the deep and profound dimensions of the same reality that challenge human inquisitiveness continue to elicit renewed spirit and novel strategies.